Enhancement of methane hydrate formation using a mixture of tetrahydrofuran and oxidized multi‐wall carbon nanotubes. (26th April 2013) - Lim, Sang‐Hoon; Riffat, Saffa B.; Park, Sung‐Seek; Oh, Seung‐Jin; Chun, Wongee; Kim, Nam‐Jin
SUMMARY Methane hydrate is a kind of gas hydrate formed by physical binding between water molecules and methane gas, which is captured in the cavities of water molecules under a specific temperature and pressure. Pure methane hydrate of 1 m3 can be decomposed into methane gas of 172 m3 and water of 0.8 m3 at standard conditions. Methane hydrate has many practical applications such as separation processes, natural gas storage transportation, and carbon dioxide sequestration. For the industrial utilization of this substance, it is essential to find a rapid method of manufacturing it. This work studies the formation of methane hydrates by using tetrahydrofuran (THF) and oxidized carbon nanotubes (OMWCNTs) by testing different fluid mixtures of THF and carbon nanotubes. The results show that when the mixed fluid contained THF, the OMWCNTs showed the gas consumption 5.2 times that of distilled water at 3.4 K subcooling. Also, THF's effects as a thermodynamic phase equilibrium promoter were preserved when it was used with OMWCNTs. Therefore, it can be expected that when OMWCNTs are used with an aqueous mixture of THF, both the favorable phase equilibrium of THF and the high gas consumption of the carbon nanotubes can be obtained. Copyright © 2013 John Wiley & Sons, Ltd.